Characteristics of Earlier Versus Delayed Presentation of Very Late Drug‐Eluting Stent Thrombosis: An Optical Coherence Tomographic Study - Seung‐Yul Lee; Jung‐Min Ahn; Gary S. Mintz; Seung‐Ho Hur; So‐Yeon Choi; Sang‐Wook Kim; Jin Man Cho; Soon Jun Hong; Jin Won Kim; Young Joon Hong; Sang‐Gon Lee; Dong‐Ho Shin; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundThe pathophysiology underlying very late drug‐eluting stent (DES) thrombosis is not sufficiently understood. Using optical coherence tomography, we investigated characteristics of very late stent thrombosis (VLST) according to different onset times. Methods and ResultsA total of 98 patients from 10 South Korean hospitals who underwent optical coherence tomography for evaluation of very late DES thrombosis were retrospectively included in analyses. VLST occurred at a median of 55.1 months after DES implantation. All patients were divided into 2 equal groups of earlier versus delayed presentation of VLST, according to median onset time. In total, 27 patients were treated with next‐generation DES and 71 with first‐generation DES. Based on optical coherence tomography findings at thrombotic sites, main VLST mechanisms were as follows, in descending order: neoatherosclerosis (34.7%), stent malapposition (33.7%), and uncovered struts without stent malapposition or evagination (24.5%). Compared with patients with earlier VLST, patients with delayed VLST had lower frequency of uncovered struts without stent malapposition or evagination (34.7% versus 14.3%, respectively; P=0.019). Conversely, the frequency of neoatherosclerosis was higher in patients with delayed versus earlier VLST (44.9% versus 24.5%, respectively; P=0.034). The frequency of stent malapposition was not different between patients with earlier and delayed VLST (34.7% versus 32.7%, respectively; P=0.831). The frequency of stent malapposition, evagination, and uncovered struts was still half of delayed VLST. ConclusionsThe pathological mechanisms of very late DES thrombosis changed over time. Delayed neointimal healing remained a substantial substrate for VLST, even long after DES implantation.